2008
DOI: 10.1016/j.nlm.2008.02.009
|View full text |Cite|
|
Sign up to set email alerts
|

Asymmetrical stimulus generalization following differential fear conditioning

Abstract: Rodent ultrasonic vocalizations (USVs) are ethologically critical social signals. Rats emit 22 kHz USVs and 50 kHz USVs, respectively, in conjunction with negative and positive affective states. Little is known about what controls emotional reactivity to these social signals. Using male SpragueDawley rats, we examined unconditional and conditional freezing behavior in response to the following auditory stimuli: three 22 kHz USVs, a discontinuous tone whose frequency and on-off pattern matched one of the USVs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 89 publications
5
49
1
Order By: Relevance
“…Similar to alarm calls in other mammals (Mateo and Holmes, 1997), 22 kHz calls in rats are not innately recognized as a distress signal (e.g. Wöhr and Schwarting, 2010;Endres et al, 2007;Bang et al, 2008) and 50 kHz vocal patterns are also influenced by experience (Wöhr et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to alarm calls in other mammals (Mateo and Holmes, 1997), 22 kHz calls in rats are not innately recognized as a distress signal (e.g. Wöhr and Schwarting, 2010;Endres et al, 2007;Bang et al, 2008) and 50 kHz vocal patterns are also influenced by experience (Wöhr et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In anticipation of pain or danger, rats often produce long bouts of calls in the 19-28 kHz range with little or no frequency modulation, which are referred to as '22 kHz calls'. The playback of 22 kHz calls causes freezing behavior (Endres et al, 2007;Allen et al, 2007;Bang et al, 2008;Kim et al, 2010;Parsana et al, 2012a,b). Vocalizations with fundamental frequencies between 28 and 90 kHz are collectively referred to as '50 kHz calls'.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency in the training protocol using one shock is likely to be based on disturbances of function in the lateral nucleus of the amygdala, since Zn 2+ and ZnT3 are present there at high levels. Recent work has demonstrated that the perirhinal cortex is involved in the processing of learned fear for context as well as trace conditioning, discontinuous tones, ultrasound vocalizations, and "complex auditory objects" (Campeau and Davis 1995;Corodimas and LeDoux 1995;Bucci et al 2000;Lindquist et al 2004;Bang et al 2008;Kholodar-Smith et al 2008b;Bang and Brown 2009). It is therefore possible that the deficiency in fear processing in ZnT3 KO mice, when a discontinuous tone is used, is based at least in part on improper function of the perirhinal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…As we are interested in general mechanisms of discrimination we chose to avoid frequencies that are close to the ones used in social communication. Furthermore, it has been shown that rats trained in a differential CS ϩ /CS Ϫ AFC protocol tend to generalize their fear responses toward 22 kHz tones, which corresponds to the fundamental frequency of alarm calls (Bang et al, 2008). Thus, the frequency of the CS ϩ was chosen to be the 10 kHz frequency (which is closer to the 22 kHz principal frequency), to avoid biasing our results toward generalization, which may arise from responses to USVs and innate fear.…”
Section: Methodsmentioning
confidence: 99%